Dough, tough, cough, rough: A "fast" fMRI localizer of component processes in reading. (October 2016) - Malins, Jeffrey G.; Gumkowski, Nina; Buis, Bonnie; Molfese, Peter; Rueckl, Jay G.; Frost, Stephen J.; Pugh, Kenneth R.; Morris, Robin; Mencl, W. Einar
Abstract: In the current study, we present a novel fMRI protocol in which words, pseudowords, and other word-like stimuli are passively presented in a rapid, sequential fashion. In this "fast" localizer paradigm, items are presented in groups of four; within sets, words are related in orthographic, phonological, and/or semantic properties. We tested this protocol with a group of skilled adult readers ( N =18). Analyses uncovered key regions of the reading network that were sensitive to different component processes at the group level; namely, left fusiform gyrus as well as the pars opercularis subregion of inferior frontal gyrus were sensitive to lexicality; several regions including left precentral gyrus and left supramarginal gyrus were sensitive to spelling-sound consistency; the pars triangularis subregion of inferior frontal gyrus was sensitive to semantic similarity. Additionally, in a number of key brain regions, activation in response to semantically similar words was related to individual differences in reading comprehension outside the scanner. Importantly, these findings are in line with previous investigations of the reading network, yet data were obtained using much less imaging time than comparable paradigms currently available, especially relative to the number of indices of component processes obtained. This feature, combined with the relatively simple nature of the task, renders it appropriate for groups of subjects with a wide range of reading abilities, including children with impairments. Highlights: We present a novel fMRI protocol for localizing the reading network. This protocol takes less imaging time than comparable paradigms currently available. The "fast" localizer is suitable for populations varying in age and skill. We demonstrate the utility of the paradigm with a group of skilled adult readers.